Characterization of fluoroacrylate palm oil polyurethane (FPOPU) with different synthesis methods using fourier-transform infra-red (FTIR) - Mohamad Ismail, Mohamad Isa; Siti Noor Hidayah, Mustapha; Rasidi, Roslan (Trans Tech Publications Ltd, 2024)
In this study, fluoroacrylate palm oil polyurethane (FPOPU) was synthesized with different synthesis methods. FPOPU was synthesized stepwise starting with the synthesis of acrylated epoxidized palm oil (AEPO) by a reaction of acrylic acid (AA) and triethylamine (TEA) as the catalyst. Then, palm oil polyurethane (POPU) was formed by the reaction of AEPO with isophorone diisocyanate (IPDI) and hydroxyethyl acrylate (HEA) as an end cap agent. POPU was further added with 1,6 hexanediol diacrylate (HDDA), trimethyloltripropane triacrylate (TMPTA), and heptafluorodecyl methyl-metacrylate (HDFDMA) monomers to form FPOPU. FPOPU synthesis methods were studied by manipulating the sequence of chemicals added, temperature, and mixing time of POPU. The FPOPU mixture was finally cast onto a silicone mold with 1 mm thickness and cured under UV radiation at 120 seconds. Based on the analysis, pre-mixed IPDI with HEA at 60°C for 15 min followed by the addition of AEPO at 60°C and further mixed for 3 hours (Method 2) shows the complete formation of the urethane chain. It is proven by the existence of NH peak at 3500 cm-1 and the disappearance of NCO peak at the range of 2200-2500 cm-1 indicating the NCO functional group has completely reacted with OH group in AEPO. The addition of fluorination also can be proved by the existence of CF stretching at 1012 cm-1. This study provides information regarding comparison between the synthesis method of FPOPU.